2006
DOI: 10.1160/th05-07-0489
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia (HIT)

Abstract: Clinical outcomes of 1,478 danaparoid treatment case reports for HIT (involving 1,418 patients) treated between 1982 and mid-2004 are analysed. Treatment in 1,291 episodes was for current HIT. Thromboembolism due to HIT was present in 39.4%. The patients include 33 children and 32 pregnancies. Two hundred twenty-six patients required extra-corporeal circuit use for renal failure, 241 patients had a concomitant thrombophilic disorder, and 351 major operations were performed. Clinical outcomes were assessed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(3 citation statements)
references
References 155 publications
0
2
0
1
Order By: Relevance
“…It is renally eliminated and has a long elimination half-life, increasing the bleeding risk [ 2 ]. In addition, cross-reactivity between danaparoid and heparin antibodies can occur and subsequently lead to new complications and unsatisfactory outcomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is renally eliminated and has a long elimination half-life, increasing the bleeding risk [ 2 ]. In addition, cross-reactivity between danaparoid and heparin antibodies can occur and subsequently lead to new complications and unsatisfactory outcomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…W przypadku niedostępności bezpośred-nich inhibitorów trombiny należy zastosować inhibitory czynnika Xa (danaparoid, rzadziej fondaparinux). Fondaparinux powinien być rozważany tylko w przypadku braku dostępności innych, alternatywnych leków, ze względu na możliwość wywoływania HIT [33,34]. Doustny bezpośredni inhibitor trombiny (dabigatran) oraz inhibitory czynnika Xa (riwaroksaban, apiksaban i edoksaban) nie reagują na HIT abs.…”
Section: Postępowanie Terapeutyczneunclassified
“…In one large retrospective study, 49% of patients with confirmed cross-reactivity experienced thromboembolic complications with an attributable death rate of 17%. Routine clinical and platelet monitoring is required, and patients with new/persistent platelet count reduction and/or new/extended thrombosis should be switched to an alternative anticoagulant [ 13 ]. That being said, the drug is no longer marketed in the US and has suffered manufacturing problems, causing a worldwide shortage in recent years [ 14 ].…”
Section: Current Guidelines For Hitmentioning
confidence: 99%